1977
DOI: 10.3189/s0022143000215608
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Fresh-Water Ice

Abstract: The principal engineering problems requiring knowledge concerning the properties of ice are prediction of the maximum force that ice might exert on a structure and determination of the load that can be placed safely on an ice cover. The properties of ice relevant to these problems are discussed. Particular attention is given to the dependence of Young's modulus on the frequency of the stress, strain-rate dependence of the yield and fracture strengths, and the ductile to brittle transition. It is shown that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…They determined the transitional strain rate at −10°C to be 10 −2 s −1 . According to compiled data by Gold [], the transitional strain rate of pure polycrystalline ice at −10°C is 10 −3 s −1 . Arakawa and Maeno [] suggested that their higher value of εfalsėnormalDtrue/normalB compared with Gold's value might be caused by confinement; their samples were slightly confined at both ends due to their setting method, and this effect caused the enhancement of transitional strain rate [ Schulson and Buck , ].…”
Section: Discussionmentioning
confidence: 99%
“…They determined the transitional strain rate at −10°C to be 10 −2 s −1 . According to compiled data by Gold [], the transitional strain rate of pure polycrystalline ice at −10°C is 10 −3 s −1 . Arakawa and Maeno [] suggested that their higher value of εfalsėnormalDtrue/normalB compared with Gold's value might be caused by confinement; their samples were slightly confined at both ends due to their setting method, and this effect caused the enhancement of transitional strain rate [ Schulson and Buck , ].…”
Section: Discussionmentioning
confidence: 99%
“…One calculated value, 1.6 MN m '2, is based on a viscoelastic deformation law for frozen ground at high stresses, a sustained rate of cooling of approximately 10øC d -• at the ground surface over durations of one to several days and a mean absolute surface temperature of-25øC [Lachenbruch, 1962]. Tensile stresses can be expected to be comparable to but slightly above the tensile strength of freshwater ice, which has values of 1 to 2 MN m '2 at loading rates greater than about 10 -5 s 'l [Gold, 1977], because lake ice generally fractures only during extreme winter cooling events [Lachenbruch, 1966]. Therefore 'r o is set to 2 MN m '2 in the reference model.…”
Section: Reference Model Parametersmentioning
confidence: 99%
“…; and Austin et al. ), while ice surface layers are treated as a geologic material and modeled using a pressure‐dependent yield surface (after Gold ).…”
Section: Experimental Approachmentioning
confidence: 99%
“…This damage model is coupled to a von Mises strength model, where the PMMA is assumed to have a yield strength of 120 MPa. The Plasticine is modeled using a pressure-dependent von Mises strength model (after Christensen et al 1968;Thomsen et al 1979;and Austin et al 1980), while ice surface layers are treated as a geologic material and modeled using a pressuredependent yield surface (after Gold 1977). Simulations also replicated conditions at much larger scale, specifically the Rock Elm impact structure (following French et al 2004).…”
Section: Numerical Modelsmentioning
confidence: 99%